2016
DOI: 10.3390/toxins8080240
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Antiaflatoxigenic Methylenedioxy-Containing Compounds and Piperine-Like Synthetic Compounds

Abstract: Twelve methylenedioxy-containing compounds including piperine and 10 piperine-like synthetic compounds were assessed to determine their antifungal and antiaflatoxigenic activities against Aspergillus flavus ATCC 22546 in terms of their structure–activity relationships. Piperonal and 1,3-benzodioxole had inhibitory effects against A. flavus mycelial growth and aflatoxin B1 production up to a concentration of 1000 μg/mL. Ten piperine-like synthetic compounds were synthesized that differed in terms of the carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…(1-(2-methylpiperidin-1-yl)-3-phenylprop-2-en-1-one) also revealed an inhibition of aflS gene expression while production of AFB1 was no longer detected (Moon et al 2016). During piperine exposure, aflT was not modulated which is in agreement with the fact that this gene is not regulated neither by aflR nor by its co-activator aflS but by other external regulators .…”
Section: Effect Of Piperine On Afb1 Gene Clustermentioning
confidence: 97%
“…(1-(2-methylpiperidin-1-yl)-3-phenylprop-2-en-1-one) also revealed an inhibition of aflS gene expression while production of AFB1 was no longer detected (Moon et al 2016). During piperine exposure, aflT was not modulated which is in agreement with the fact that this gene is not regulated neither by aflR nor by its co-activator aflS but by other external regulators .…”
Section: Effect Of Piperine On Afb1 Gene Clustermentioning
confidence: 97%
“…These strategies range from good agricultural practices to the use of biocontrol agents or natural compounds able to block toxin production [10]. Even if the exact mechanism of action has not yet been completely elucidated, a few studies already demonstrated that some of these natural products can inhibit AFB1 production by a transcriptional down-regulation of the genes involved in AFB1 synthesis [11][12][13][14][15][16][17][18]. Aflatoxins are the product of a complex biosynthesis pathway involving at least 27 enzymatic reactions [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, effective control strategies for fungal infection and toxin production should be organized for the right place and time [19]. Chemical treatment has been seriously considered as an effective method to reduce fungal infection and toxin production in agricultural foods and feedstuffs [9,15,20].…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of the antifungal activities of the two test compounds were conducted according to a previous report [15]. Briefly, spores, equivalent to 10 6 of A. flavus, were transferred into PDB liquid culture media (25 mL), and the test compounds were added to the liquid media.…”
Section: Measurement Of the Antifungal Activities Of The Test Compoundsmentioning
confidence: 99%
See 1 more Smart Citation